2010
DOI: 10.1002/cphc.200900902
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Proline and Glycine on the TiO2(110) Surface: A Density Functional Theory Study

Abstract: The optimal adsorption modes for the amino acids glycine and proline on the ideal TiO(2)(110) surface are investigated by using density functional theory (PBE) applying periodic boundary conditions. Binding modes with anionic acid moieties bridging two titanium atoms after transferring a proton to the surface are the most stable configurations for both molecules investigated-similar to previous results for carboxylic acids. In contrast to the latter compounds, amino acids can form hydrogen bonds via the amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 68 publications
3
62
0
Order By: Relevance
“…Tonner [293]confirmed the trend found by Ojamae [289], but a new anionic adsorption mode ( Figure 78b) was identified as being even more stable by 9 kJmol -1 (0.1 eV/molecule) compared to the previous minimum configuration, this time in agreement with the STM study of Qiu and Barteau which suggested adsorption in the anionic form. Among the other considered configurations, the anionic bifunctional adsorption with COO and NH 2 binding to Ti atoms in a bridging mode was found 23 kJ/mol (0.2 eV/molecule) less stable than the most favoured configuration.…”
Section: Glycine On Tiosupporting
confidence: 79%
See 3 more Smart Citations
“…Tonner [293]confirmed the trend found by Ojamae [289], but a new anionic adsorption mode ( Figure 78b) was identified as being even more stable by 9 kJmol -1 (0.1 eV/molecule) compared to the previous minimum configuration, this time in agreement with the STM study of Qiu and Barteau which suggested adsorption in the anionic form. Among the other considered configurations, the anionic bifunctional adsorption with COO and NH 2 binding to Ti atoms in a bridging mode was found 23 kJ/mol (0.2 eV/molecule) less stable than the most favoured configuration.…”
Section: Glycine On Tiosupporting
confidence: 79%
“…In contrast, proline appears to be strongly adsorbed on the defected (001) surface, as evidenced by a shift of the desorption temperature from 350 K on stoichiometric TiO 2 (001) to 530-550 K on the oxygen-defected surface. Theoretical calculations reveal that proline shows similar adsorption behaviour than glycine but zwitterionic forms and coordination via the nitrogen atom are much less viable [293]. The most stable mode for both molecules is theone schematized in Figure 77, with an anionic amino acid moiety bridging two surface titanium atoms via the carboxyl oxygen atoms and a proton transferred to an oxygen atom at the surface.…”
Section: Glycine and Water Onmentioning
confidence: 99%
See 2 more Smart Citations
“…DFT calculations by Tonner resulted in a similar tilting stabilisation effect of the surface bound hydrogen atom and the nitrogen atom of the amino group [11]. It is interesting that in the case of calculations including vdW interactions, the "vertical" configurations AN(OO) and ZW(OO) are not minima in the adsorption landscape.…”
Section: Adsorption Of Glycinementioning
confidence: 85%